2022
DOI: 10.1002/bies.202100212
|View full text |Cite
|
Sign up to set email alerts
|

Can aggressive cancers be identified by the “aggressiveness” of their chromatin?

Abstract: Phenotypic plasticity is a crucial feature of aggressive cancer, providing the means for cancer progression. Stochastic changes in tumor cell transcriptional programs increase the chances of survival under any condition. I hypothesize that unstable chromatin permits stochastic transitions between transcriptional programs in aggressive cancers and supports non‐genetic heterogeneity of tumor cells as a basis for their adaptability. I present a mechanistic model for unstable chromatin which includes destabilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 169 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that chromatin motion plays an important role in maintaining interactions between topologically associated domains (TADs) for an average of 10 min to facilitate gene expression and this was shown to be enabled by cohesin and CTCF (Mach et al 2022 ). Fluctuations in chromatin dynamics can have profound effects on gene expression and contribute to the onset or progression of diseases, such as cancer (Guasconi and Ait‑Si-Ali 2004 ; Gurova 2022 ; Li et al 2022 ). Hence, understanding the mechanisms that underlie chromatin architecture and dynamics is of paramount importance, which requires strategies to label and visualize DNA in an unbiased genome-wide manner in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that chromatin motion plays an important role in maintaining interactions between topologically associated domains (TADs) for an average of 10 min to facilitate gene expression and this was shown to be enabled by cohesin and CTCF (Mach et al 2022 ). Fluctuations in chromatin dynamics can have profound effects on gene expression and contribute to the onset or progression of diseases, such as cancer (Guasconi and Ait‑Si-Ali 2004 ; Gurova 2022 ; Li et al 2022 ). Hence, understanding the mechanisms that underlie chromatin architecture and dynamics is of paramount importance, which requires strategies to label and visualize DNA in an unbiased genome-wide manner in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of BioEssays , an article by Katerina Gurova outlines strategies to identify aggressive cancer subtypes based on chromatin state. [ 1 ] The central hypothesis states that the ability of tumor cells to adapt and survive is a result of “unstable” chromatin that creates a permissive environment for stochastic gene expression. Particularly, aggressive cancers have decondensed chromatin, which results in greater chromatin mobility within the nucleus and increased probability of productive enhancer and promoter interactions.…”
mentioning
confidence: 99%
“…[1] The idea of the preferential germline-like transformation of somatic cancer cells contrasts with another currently discussed hypothesis stipulating that hypomethylated and 'unstable' chromatin promotes stochastic gene expression changes leading to its 'aggressiveness ' , increasing malignancy and spread of the tumour. [5] Bruggeman et al are experts in germ cell biology, hence, they argue eloquently for a non-random activation of meiotic genes in cancer, and provide a great deal of supporting evidence from their own bioinformatic analysis of hallmark germline features in several somatic cancers. [1] The jury is still out which of the two concepts is most plausible, and detailed mechanistic studies of cancer cells in humans and other species are needed to establish which events -genomic rearrangements linked to induction of meiosis -or rather epigenetic adaptation -are the first events triggering malignant transformation of somatic cells.…”
mentioning
confidence: 99%
“…[ 1 ] The idea of the preferential germline‐like transformation of somatic cancer cells contrasts with another currently discussed hypothesis stipulating that hypomethylated and ‘unstable’ chromatin promotes stochastic gene expression changes leading to its ‘aggressiveness ’, increasing malignancy and spread of the tumour. [ 5 ] Bruggeman et al. are experts in germ cell biology, hence, they argue eloquently for a non‐random activation of meiotic genes in cancer, and provide a great deal of supporting evidence from their own bioinformatic analysis of hallmark germline features in several somatic cancers.…”
mentioning
confidence: 99%